Loading web-font TeX/Math/Italic

x(-37+x)=0

Simple and best practice solution for x(-37+x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(-37+x)=0 equation:



x(-37+x)=0
We add all the numbers together, and all the variables
x(x-37)=0
We multiply parentheses
x^2-37x=0
a = 1; b = -37; c = 0;
Δ = b2-4ac
Δ = -372-4·1·0
Δ = 1369
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
x_{1}=\frac{-b-\sqrt{\Delta}}{2a}
x_{2}=\frac{-b+\sqrt{\Delta}}{2a}

\sqrt{\Delta}=\sqrt{1369}=37
x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-37)-37}{2*1}=\frac{0}{2} =0
x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-37)+37}{2*1}=\frac{74}{2} =37

See similar equations:

| 3x²-6x=0 | | 9x+2.3=-12.3 | | 5/v=2/7.25 | | 62x+56=58.80 | | 3=1v-4+8v-36 | | -.1x^2+112x-3000=0 | | x^2+103x+603=0 | | 5k-(7+k)=-(9k+7) | | 90-3x=0 | | x|-5=3 | | 3x+60=81 | | 90-x=0 | | K=(4x-2)-7 | | 6x^2-25x-12=0 | | 9z-6=23z-14 | | 8y(2y+4)=102 | | x^2+11/2x=1/2 | | 12x-12=6(3x) | | (5x/2)−4=(2x−7/6) | | 2y+4=-18-9y | | 7+4(3x-6)=-5(2x+1) | | 9y+53=8 | | 27.79=5g+3.94 | | x^2+10=54 | | 4y+53+5y=26+ | | 5x+4Y=95 | | 4x/3-1=19 | | 6/11=36x | | 1/2(6+-z)=z | | 35=4v+8 | | 31.64=6g+3.74 | | 76=20+7c |

Equations solver categories